2020
DOI: 10.26418/coding.v8i3.42409
|View full text |Cite
|
Sign up to set email alerts
|

Optimasi Pencarian Rute Terpendek Distribusi Barang Menggunakan Metode Simulated Annealing (Studi Kasus: Pd Bumi Jaya Indah Kota Pontianak)

Abstract: PD Bumi Jaya Indah adalah sebuah perusahaan yang bergerak di bidang jasa dan berperan sebagai distributor barang brand ABC di kota Pontianak. Permasalahan dalam pengantaran barang yang dilakukan PD Bumi Jaya Indah yaitu rute yang ditempuh tidak optimal akan berdampak pada jarak, biaya dan waktu pengantaran sehingga diperlukan sebuah metode optimasi yang dapat memaksimalkan solusi agar didapatkan hasil dan proses yang optimal. Metode Simulated Annealing adalah satu diantara algoritma optimasi yang dapat menjadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Addressing the limitations of earlier studies, this research endeavors to comprehensively map all street segments in Pontianak using the space syntax method. This approach counters the shortcomings of Utami et al (2014) research, which identified the shortest paths for firefighter vehicle movement but was constrained to only 49 designated points. The complexity of Pontianak's route system and the random nature of fire accidents rendered previous approaches ineffective in optimizing optimal paths.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the limitations of earlier studies, this research endeavors to comprehensively map all street segments in Pontianak using the space syntax method. This approach counters the shortcomings of Utami et al (2014) research, which identified the shortest paths for firefighter vehicle movement but was constrained to only 49 designated points. The complexity of Pontianak's route system and the random nature of fire accidents rendered previous approaches ineffective in optimizing optimal paths.…”
Section: Discussionmentioning
confidence: 99%